Cyberchondria, Covid-19 phobia, and well-being: a relational study on teachers - Karakaş, Neşe; Tekin, Çiğdem; Bentli, Recep; Demir, Ekrem (La Medicina del Lavoro, 2022)
Background: This study aims at investigating level and contributor factors of Cyberchondria, Covid-19-related Phobia, and Well-Being in a sample of teachers in Turkey. Methods: The study was conducted on teachers (n=1000) working in a province in eastern Turkey. Data for the study were collected using a form that included participants’ descriptive characteristics, the Covid-19 Phobia Scale (C19P-SE), the Cyberchondria Severity Scale, and the World Health Organization-5 Well-Being Index (WHO-5). Spearman correlation analysis, Mann-Whitney U test, and Kruskal Wallis analysis of variance were used to analyze the data. Results: As participant’s cyberchondria levels rose, C19P-SE scores increased (r=0.271, p